Neisseria meningitidis serogroup B lipopolysaccharides induce a lower pro-inflammatory effect within the proteoliposome used in Cuban anti-meningococcal vaccines - Pérez, O.; Graham, S.; Lastre, M.; Ellis, C. D.; Pupo, R. R.; Tellez-Martínez, D. [UNESP]; Batista-Duharte, A. [UNESP] (Elsevier, 2018)
Neisseria meningitidis outer membrane vesicles or proteoliposomes (PLs) have been used as vaccines and adjuvants. Despite the presence of potentially toxic amounts of lipopolysaccharide (LPS), they have been shown to be safe, well tolerated, and immunogenic. This suggests that LPS-PL may have reduced LPS toxicity. In this study, it is shown that the ability of PL to induce pro-inflammatory cytokine production in human U937 histiocytic cell line is significantly lower than that of an equivalent concentration of purified LPS. This demonstrates that certain components or physical properties of PL reduce the pro-inflammatory activity of their endogenous LPS. To investigate the mechanisms responsible for this protective effect, PLs were fractionated and an assessment was made of the ability of the resulting fractions to induce inflammatory cytokine expression. Several individual PLs fractions were more potent inducers of pro-inflammatory cytokine production than the non-fractionated PLs. The majority of the pro-inflammatory activities appeared to be mediated by the presence of LPS in the fractions, as shown by the ability of an anti-CD14 antibody to block it. However, in two PL fractions, the production of IL-8, and to a lesser extent IL-6, was not inhibited by anti-CD14 treatment, indicating that pro-inflammatory components other than LPS could also be present in PL. Eight proteins present in the fractions were identified by n-terminal sequencing. The results of this study suggest that two of them, PorB, and in particular, the RmpM protein, may also contribute to the pro-inflammatory activity of N. meningitidis PL. These results could support the development of PLs as vaccine adjuvant.
Los lipopolisacáridos de Neisseria meningitidis serogrupo B inducen un reducido efecto proinflamatorio dentro del proteoliposoma usado en vacunas cubanas antimeningocócicas
Keywords: Adjuvant; LPS; Neisseria meningitidis; Pro-inflammatory cytokines; Proteoliposome